PENGUATAN NILAI KARAKTER BAKTI ANAK TERHADAP ORANG TUA UNTUK GEN Z MELALUI ANIMASI 3D UWAIS AL-QARNI - Wafiy Anwarul Hikam; Utama, Isma Izha; Arifin, Miftahul; Maharani, Elfira Putri; Nugroho, Fresy; Karami, Ahmad Fahmi (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2025)
This study examines the implementation of the value of devotion to parents through educational animation media, focusing on the inspiring story of Uwais al-Qarni. Uwais al-Qarni is known in Islamic history as a figure who showed extraordinary dedication to his mother. In an effort to revive these values, we developed an animation that aims to educate and inspire the audience, especially the younger generation. The animation creation process includes in-depth literature research, scenario and storyboard development, character design, and animation production and editing. The result is an animated work that is not only entertaining but also conveys a strong moral message about the importance of devotion to parents. Initial trials showed that this animation was effective in increasing audience awareness and understanding of these values. This study makes a significant contribution to the field of character education through digital media and demonstrates the potential of animation as an effective and engaging educational tool.